Analisis Tingkat Keterpaparan Kegiatan Prolanis Pasien DM Tipe 2 Pada Dua Puskesmas Kota Bekasi - Warti, Lia WARTI, (Jurnal Ayurveda Medistra, 2023)
Chronic Disease Management Program (Prolanis) is a government program in the health service system that is implemented in an integrated manner and involves participants, health facilities and BPJS Kesehatan. Prolanis' goal is to encourage chronic disease participants to achieve an optimal quality of life so as to prevent complications. The implementation of Prolanis activities at a Health Facility may be different from other Health Facilities. To determine the success of implementing Prolanis activities at Health Facilities can be done by analyzing the level of exposure of Prolanis activities to type 2 DM patients at both puskesmas in Bekasi city. This study aims to analyze the exposure level of Prolanis activities in type 2 DM patients at PKM A and PKM B. The research method was descriptive analytic observational and was carried out in PKM A and PKM B with a total of 80 patients as respondents consisting of 40 type 2 DM patients at PKM A and 40 type 2 DM patients at PKM B within 1 (one) month. Prolanis activity data for each health center were collected using a questionnaire that met the validity and reliability test requirements. Prolanis activities carried out at the two puskesmas included medical consultations, club activities (gymnastics), group education, SMS gateways, home visits and health status monitoring. The results showed that the exposure level of Prolanis activities in PKM A was higher than PKM B.